A ski robot system for qualitative modelling of the carved turn - Yoneyama, T.; Kagawa, H.; Unemoto, M.; Iizuka, T.; Scott, N. W. (Sports Engineering, 2009)
A robot that simulates a number of human leg joint motions during carved turns has been developed. Each leg had six degrees of freedom like those of human athletes. An on-board computer controlled the sequence of joint angles in an open-loop mode during skiing on an artificial grass slope. The relations among joint motions, reacting forces and turn trajectory were investigated by programming various motions of the robot. At first, the effect of basic joint motions, such as abduction-adduction and flexion-extension of the hip, knee and ankle joints were investigated. Then the sequence of a top athlete`s joint motions, measured in a separate study, was applied to investigate its effect on the ski turn. The human-inspired programme produced a more even force balance between the skis and also a higher-quality turn. The requirements for a successful physical model of a human skier are discussed.